Associations between peak oxygen uptake, lung function, and bronchiectasis in children with cystic fibrosis in the era of CFTR modulators. Issue 6 (1st February 2021) - Du Berry, Cassidy; Westrupp, Nicole; Shanthikumar, Shivanthan; Welsh, Liam
Abstract: Background: With the emergence of cystic fibrosis transmembrane conductance regulator (CFTR) modulators, forced expiratory volume in 1 s (FEV1 ) may become a less sensitive measure of pulmonary disease progression in children with cystic fibrosis (CF). Increasing evidence shows that peak oxygen uptake (VO2peak ) is a strong predictor of prognosis in CF. The primary aim of this study was to describe the associations between peak oxygen uptake, lung function, and bronchiectasis in children with CF in the era of CFTR modulators. Methods: Spirometry and a maximal cardiopulmonary exercise test (CPET) were performed on the same day and compared to markers of disease severity. Markers of disease severity included a number of pulmonary exacerbations resulting in hospital admission within the preceding 12 months, body mass index, Pseudomonas aeruginosa ( PsA ) infection, and bronchiectasis. Results: Fifty‐two subjects (24 female) with CF participated in the study with a mean ( SD ) age of 13.8 (2.4) years, range 8–18 years. Forty‐nine participants met satisfactory criteria for a maximal CPET. A significant correlation was found between relative VO2peak %predicted and FEV1 %predicted ( r  = .546, p  < .001). A total of 4/49 children demonstrated an impaired aerobic capacity despite normal spirometry. Participants who had experienced one or more pulmonary exacerbations in the previous 12 months had a significantly lower relative VO2peak %predicted ( p  = .02). Conclusions: In children with CF who have mild pulmonary disease, there is significant correlation between FEV1 and VO2peak . In all, 8.2% of participants had an abnormal CPET result despite normal spirometry, and preceding pulmonary exacerbations were associated with poorer CPET outcomes. CPET may offer important prognostic information for clinical decision making in this new era of CFTR modulators.